The role of increased post-impact ball speed on plantar pressure during open and square stance groundstrokes in female tennis players - Lambrich, J.; Muehlbauer, T. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background It is firmly established that achieving a high ball speed during the execution of groundstrokes represents a relevant factor for success in tennis. However, little is known about how plantar pressure changes as post-impact ball speed is increased during open and square stance groundstrokes. The objective of the study was to determine how tennis players change the plantar pressure in each foot when they execute open versus square stance forehand groundstrokes in order to increase post-impact ball speed.